Trophic niche overlap between native freshwater mussels (Order: Unionida) and the invasive Corbicula fluminea. Issue 8 (31st May 2021) - Modesto, Vanessa; Dias, Ester; Ilarri, Martina; Lopes‐Lima, Manuel; Teixeira, Amílcar; Varandas, Simone; Castro, Paulo; Antunes, Carlos; Sousa, Ronaldo
Abstract: Freshwater mussels (Order Unionida) are highly threatened. Interspecific competition for food sources with invasive alien species is considered to be one of the factors responsible for their decline because successful invaders are expected to have wider trophic niches and more flexible feeding strategies than their native counterparts. In this study, carbon (δ 13 C: 13 C/ 12 C) and nitrogen (δ 15 N: 15 N/ 14 N) stable isotopes were used to investigate the trophic niche overlap between the native freshwater mussel species, Anodonta anatina, Potomida littoralis, and Unio delphinus, and the invasive bivalve Corbicula fluminea living in sympatry in the Tua basin (south‐west Europe). The species presenting the widest trophic niches were C. fluminea and A. anatina, which indicate that they have broader diets than U . delphinus and P. littoralis . Nonetheless, all the species assimilated microphytobenthos, sediment organic matter, and detritus derived from vascular plants, although with interspecific variability in the assimilated proportions of each source. The trophic niche of the invasive species overlapped with the trophic niche of all the native species, with the extent varying between sites and according to the species. From the three native species analysed, Potomida littoralis may be at a higher risk for competition for food with C. fluminea in the Tua basin, if food sources become limited, because this native mussel presented the narrowest trophic niche across sites and the highest probability of overlapping with the trophic niche of C. fluminea . Given the global widespread distribution of C. fluminea, the implementation of management measures devoted to the control or even eradication of this invasive alien species should be a conservation priority given its potential for competition with highly threatened native freshwater mussels.